Analysis of the scanning performance of dental implants using different intraoral scanners: Accuracy study - Briza Letícia Almeida-Silva; Sérgio Candido-Dias; Geraldo Alberto Pinheiro de Carvalho; Aline Batista Gonçalves-Franco; Kelly Maria Silva-Moreira; Elimario Venturin-Ramos (International Journal of Interdisciplinary Dentistry, 2025)
The accuracy of intraoral scanners in scanning dental implants in different clinical situations was verified. Models simulating single rehabilitation, multiple fixed partial dentures and protocol were scanned with each scanner by a single trained operator (n=10): iTero (Align Technology), Trios (3Shape), CEREC Primescan (Dentsply Sirona) and Ceramill 400 laboratory scanner (Amann Girrbach), as a control group. The engineering software R everse (Geomagic) was used for the analysis of the files obtained and SPSS for the statistics (p≤0.05). In single-prosthesis rehabilitation, there was no difference between the intraoral scannersiTero, Trios and CEREC Primescan intraoral scanners. In the multiple fixed partial dentures, the Trios and CEREC Primescan scanners showed significantly smaller discrepancies than those found with the iTero, only the CEREC Primescan intraoral scanner did not differ significantly from the benchtop scanner. Simulating protocol-type prosthesis, in any region, all intraoral scanners resulted in significantly less accurate measurements than the benchtop scanner. Exceptions were found when the CEREC Primescan scanner was used in the regions of elements 13-23, 16-26 and 16-13, situations in which there was no significant difference in relation to the benchtop scanner. Therefore, different intraoral scanners and clinical situations can influence the accuracy of dental implant scanning.